Theoretical Studies of a Centrifugal Pneumatic Separator with Horizontal Air Flow. Issue 1 (September 2021) - Chernyakov, A V; Koval, V S; Begunov, M A; Algazin, D N; Boytsov, K A
Abstract: The article is devoted to the study of the motion of grain heap particles along the cylindrical surface of the separator. This article substantiates the relevance of post-harvest grain processing in the agro-industrial complex, proposes a design of a centrifugal pneumatic separator with a horizontal air flow, and describes the process of its operation. A mathematical model is obtained for the motion of a grain heap particle along the cylindrical surface of a grain separator with a centrifugal horizontal air flow.